Wzory do naśladowania w budowaniu kultury rzetelności naukowej. Komunikat z badań w projekcie Path2Integrity - Dwojak-Matras, Agnieszka; Kalinowska, Katarzyna; Koterwas, Agnieszka (Człowiek i Społeczeństwo, 2021)
The subject of the text is the use of role models in building an academic culture of research integrity. We present some possible ways of involving them in teaching and promoting research integrity at universities. The acquired empirical results concern the qualities of a scientist worthy of emulation indicated by undergraduates, postgraduates and PhD students. The qualitative analysis of the collected data enabled us to describe two profiles of a good scientist: an accessible one, who sets an example to his/her mentees in a direct relationship, and a distant one, admired because of his/her work ethos and outstanding achievements. The research was conducted as an online survey in 2020 as part of the project